1998
DOI: 10.1046/j.1365-2672.1998.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of small volume microbial suspensions in an ultrasonic standing wave

Abstract: The removal of Saccharomyces cerevisiae and Escherichia coli from 2.5 ml suspensions in ultrasonic standing wave formed at 1 or 3 MHz has been characterized. The standing wave was set up by a plane transducer and reflector mounted in the vertical plane. Cells in the ultrasonic field first concentrated in vertical planes at half wavelength separations. The ultrasound was then pulsed to allow clumps of concentrated cells to sediment in a controlled way during the short 'off' intervals. Yeast removal from suspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…In this way the perfusion flow can be maintained without loss of the reactor contents. Similar modes of operation can be found in a range of other work 29,30 .…”
Section: Gravitational Forcessupporting
confidence: 77%
“…In this way the perfusion flow can be maintained without loss of the reactor contents. Similar modes of operation can be found in a range of other work 29,30 .…”
Section: Gravitational Forcessupporting
confidence: 77%
“…One utilisation of particle manipulation by ultrasonic radiation which has been developed during the last decade up to successful application in industrial environments is the Ultrasonically Enhanced Settling (U.E.S.) for filtration purposes (Grö schl, 1998;Limaye, 1998;Trampler, 1999;Gorenflo, 2005;Dalm, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, in some high throughput studies with PDMS materials, it can go up to 10 W [97] which requires an additional external cooling of the piezoelectric material and the channel. The use of aluminum block as a heat sink may be applied [85,97,110].…”
Section: Hardwarementioning
confidence: 99%
“…Cell viability has also been assessed after acoustic separation or manipulation processes. In order to determine the viability of bio-particles, trypan blue was used, and it was observed that the cells were not negatively affected from acoustic manipulation process [81,86,92,110] as they were viable after being exposed to ultrasonic waves. Referring to the strong suits of the ACT methods, an ACT diagnosis device has already commercialized (Attune Acoustic Focusing Cytometer by Life Sciences, www.lifetechnologies.com).…”
Section: Applicationmentioning
confidence: 99%